Financial sustainability issues in Malaysia’s telecentres - Ibrahim, Huda; Yasin, Azman; Md Dahalin, Zulkhairi (Canadian Center of Science and Education, 2010)
Telecentres plays an important role in bridging digital divide in Malaysia. A study was conducted to identify the issues of financial sustainability on 132 telecentres in Malaysia. The study focused on TCs in four regions of Malaysia Peninsular (northern, central, southern and eastern). Questionnaires were sent to the telecentres’ operators. The results prove that financial support is critical in operating and maintaining the centers. The costs incurred in running telecentres involve the costs for promotion, staff, utilities, premise renting, and training. More than 75 percent of the telecentres are operating under tight cash budget. Recommendations are given to encourage telecentre’s financial sustainability in the future.